Diprotodon on the sky. The Large Galactic Supernova Remnant (SNR) G278.94+1.35 - Filipović, Miroslav D.; Lazarević, Sanja; Araya, Miguel; Hurley-Walker, Natasha; Kothes, Roland; Sano, Hidetoshi; Rowell, Gavin; Martin, Pierrick; Fukui, Yasuo; Alsaberi, Rami Z.E.; Arbutina, Bojan; Ball, Brianna; et al. (Publications of the Astronomical Society of Australia, 2024)
We present a re-discovery of G278.94+1.35a as possibly one of the largest known Galactic supernova remnants (SNRs) - that we name Diprotodon. While previously established as a Galactic SNR, Diprotodon is visible in our new Evolutionary Map of the Universe (EMU) and GaLactic and Extragalactic All-sky MWA (GLEAM) radio continuum images at an angular size of, much larger than previously measured. At the previously suggested distance of 2.7 kpc, this implies a diameter of 157 152 pc. This size would qualify Diprotodon as the largest known SNR and pushes our estimates of SNR sizes to the upper limits. We investigate the environment in which the SNR is located and examine various scenarios that might explain such a large and relatively bright SNR appearance. We find that Diprotodon is most likely at a much closer distance of 1 kpc, implying its diameter is 58 56 pc and it is in the radiative evolutionary phase. We also present a new Fermi-LAT data analysis that confirms the angular extent of the SNR in gamma rays. The origin of the high-energy emission remains somewhat puzzling, and the scenarios we explore reveal new puzzles, given this unexpected and unique observation of a seemingly evolved SNR having a hard GeV spectrum with no breaks. We explore both leptonic and hadronic scenarios, as well as the possibility that the high-energy emission arises from the leftover particle population of a historic pulsar wind nebula.
CRIS-Team Scopus Importer:2025-02-04
Keywords: gamma rays: gammaray sources; HI line emission: ISM; radiation mechanism: non-thermal; radio continuum: ISM; radio continuum: radio sources; SNR: individual (Diprotodon)